غیرت کی اخلاقی حیثیت اور ادیان عالم میں غیرت کے تصورکا تجزیاتی مطالعہ: THE MORAL STATUS OF GHAYRAH AND AN ANALYTICAL STUDY OF THE CONCEPT OF HONOR IN WORLD RELIGIONS (Al-Aasar, 2025)
This study presents an analytical examination of the moral status of ghayrah (moral jealousy) and explores its understanding across different nations and world religions. The discussion begins by distinguishing between objective morality, which holds moral values as universal and unchanging, and subjective morality, which views right and wrong as relative to individuals or societies. The subjective morality fails to provide a stable moral framework, while objective morality requires a higher, transcendent standard. From the Islamic perspective, this ultimate moral authority is God, whose guidance defines what is truly good or evil.Within this framework, ghayrah is evaluated as either praiseworthy or blameworthy based on divine guidance. The study reviews the concept of honor and moral zeal in major religions and civilizations, including Hinduism, Buddhism, Zoroastrianism, Judaism, Christianity, and pre-Islamic Arab, Persian, and Byzantine societies. It highlights how distortion of divine teachings led many societies to either extreme harshness, injustice, or moral laxity under the name of honor. In contrast, Islam introduced a balanced and ethical understanding of ghayrah, setting clear limits that prevent oppression while promoting modesty, dignity, justice, and social responsibility.The paper concludes that ghayrah is a fundamental moral value essential for personal integrity and social stability. When guided by justice and moderation, it protects human dignity; when misused, it leads to moral corruption.